Sustainable Tourism 2019
DOI: 10.4018/978-1-5225-7504-7.ch020
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Rural Tourism of Lower Danube Region in Serbia

Abstract: Sustainable tourism implies preserved space, prevents ecological and socio-cultural devastation, but at the same time encourages tourism development. Their application and adequate implementation increases the chance of a tourist destination that will be able to develop sustainable tourism, so the aim of this paper is to separate characteristics and principles of sustainability on certain areas and to show their advantages and limitations. In this paper are introspected factors of tourism development, both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Observing Vojvodina, there are relevant potentials for the development of rural tourism because this territory is famous for its rural areas, granges, and numerous small settlements with their distinctive narrow streets. Fruška Gora and Vršac Mountains create the possibility for the development of mountain tourism [39]. The cities of Belgrade and Novi Sad are the leading city destinations in Serbia, and due to their vicinity, they represent important outgoing centers for destinations in Vojvodina.…”
Section: Area Studymentioning
confidence: 99%
“…Observing Vojvodina, there are relevant potentials for the development of rural tourism because this territory is famous for its rural areas, granges, and numerous small settlements with their distinctive narrow streets. Fruška Gora and Vršac Mountains create the possibility for the development of mountain tourism [39]. The cities of Belgrade and Novi Sad are the leading city destinations in Serbia, and due to their vicinity, they represent important outgoing centers for destinations in Vojvodina.…”
Section: Area Studymentioning
confidence: 99%
“…The simplest division of events is based on their importance and size, dividing the events into the local, regional, national, and international. For Štetić (2007), this division does not provide an answer about the character of events. Boldwin et al (2006) identified four basic groups of events: local, main, hallmark, and mega events.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Getz (2008) and Getz and Page (2016) divided events into the local, regional, periodic or hallmark, and occasional mega events. Today, the most developed types of events are: educational and science, cultural, political, entertainment, business, private, and sport-events (Boldwin et al, 2006; Damster et al, 2005; Getz, 2008; Štetić, 2007).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…In the same year, the average monthly net salary in BP region was slightly below the national level, with a significant difference in unemployment rates by area (18.8% in Podunavlje and 13.5% in Braničevo), Podunavlje area participated in GVA of the Republic of Serbia with 1.4% and Braničevo with 2.0% and nearly 76,000 tourists visited the region [52,55,56]. Braničevo area relies on the valuable tourism potential of the Danube River and natural and historical sites in the hinterland (Djerdap National Park and UNESCO Global Geopark, Homolje Mountains, Viminacium, medieval fortressess, monasteries) [44,[57][58][59].…”
Section: Geography Population and Economymentioning
confidence: 99%